Left globus pallidus abnormality in never-medicated patients with schizophrenia. - Early, T S (1987)
Schizophrenia is a severe psychiatric disorder characterized by onset in young adulthood, the occurrence of hallucinations and delusions, and the development of enduring psychosocial disability. The pathophysiology of this disorder remains unknown. Studies of cerebral blood flow and metabolism designed to identify brain abnormalities in schizophrenia have been limited by inadequate methods of anatomical localization and the possibility of persistent medication effects. We have now used positron emission tomography and a validated method of anatomical localization in an attempt to identify abnormalities of regional cerebral blood flow in newly diagnosed never-medicated patients with schizophrenia. An exploratory study of 5 patients and 10 normal control subjects identified abnormally high blood flow in the left globus pallidus of patients with schizophrenia. A replication study of 5 additional patients and 10 additional control subjects confirmed this finding. No other abnormalities were found.